2014
DOI: 10.3732/ajb.1400359
|View full text |Cite
|
Sign up to set email alerts
|

Pollination of Vietnamese Aspidistra xuansonensis (Asparagaceae) by female Cecidomyiidi flies: Larvae of pollinator feed on fertile pollen in anthers of anthetic bisexual flowers

Abstract: More than one kind of myiophily is present in Aspidistra. Brood site pollination was documented for the first time in Aspidistra. The pollination system of A. xuansonensis differs from other kinds of brood site pollination in the exit of the larvae prior to the decomposition of floral parts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 64 publications
3
15
0
Order By: Relevance
“…According to the present data and previous studies (Vislobokov et al , ), all investigated species of Aspidistra possess similar flowering phenology. The flower remains anthetic for 4–12 days and is visited by insects during the first 4–7 days.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…According to the present data and previous studies (Vislobokov et al , ), all investigated species of Aspidistra possess similar flowering phenology. The flower remains anthetic for 4–12 days and is visited by insects during the first 4–7 days.…”
Section: Discussionsupporting
confidence: 89%
“…The first field observations confirmed the suggestion of occurrence of myiophily within the genus Aspidistra but did not reveal any detail about the reward and attraction of the pollinator. The most recent study in northern Vietnam showed that A. xuansonensis is pollinated by female gall midges (Cecidomyiidae) (Vislobokov et al ). The mechanism of pollination in A. xuansonensis was recognized as unique.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While it is assumed that the short-lived adults of most cecidomyiids do not feed [ 4 ], some are known to consume nectar or pollen from flowers, and may effect pollination (e.g., [ 39 ], [ 40 ]). This is in contrast to cecidomyiid species that effect pollination by using flowers as oviposition sites rather than a food source for the adults (e.g., [ 41 43 ]). In the case of Ozirhincus , because the females spend some time on the inflorescences when ovipositing into flowers, they end up carrying some pollen grains on their body, and possibly contribute towards pollination, but we do not know if they actually feed on the flowers by inserting their proboscis into them.…”
Section: Discussionmentioning
confidence: 98%